2012
DOI: 10.1111/j.1365-2478.2012.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Permeability inversion from low‐frequency seismoelectric logs in fluid‐saturated porous formations

Abstract: A B S T R A C TIn this paper, a method is proposed to invert permeability from seismoelectric logs in fluid-saturated porous formations. From the analysis of both the amplitude and the phase of simulated seismoelectric logs, we find that the Stoneley wave amplitude of the ratio of the converted electric field to the pressure (REP) is sensitive to porosity rather than permeability while the tangent of the REP's phase is sensitive to permeability. The REP's phase reflects the phase discrepancy between the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…The magnitude of seismo electric current depends on porosity, pore size, zeta potential of the pore surfaces, and elastic properties of the matrix was investigated by [4]. The tangent of the ratio of converted electic field to pressure is approximately in inverse proportion to permeability was studied by [5]. Permeability inversion from seismoelectric log at low frequency was studied by [6].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of seismo electric current depends on porosity, pore size, zeta potential of the pore surfaces, and elastic properties of the matrix was investigated by [4]. The tangent of the ratio of converted electic field to pressure is approximately in inverse proportion to permeability was studied by [5]. Permeability inversion from seismoelectric log at low frequency was studied by [6].…”
Section: Introductionmentioning
confidence: 99%
“…As it does not exist outside the seismic disturbance, the coseismic wavefield only provides local information restricted to the vicinity of the dipole receivers: when these are deployed inside a borehole, the study of coseismic effects may provide valuable information about the medium’s porosity and permeability near the borehole at depth (Dupuis & Butler 2006; Hu et al. 2007; Guan et al. 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The measured amplitude of the normalized coefficient on sandstones is in the range of 1.6 × 10 showed that the normalized coefficient could detect a 0.5 mthick bed of permeability 10 −13 m 2 within a formation of permeability 10 −15 m 2 . On the other hand, Guan et al (2013) modelled the coseismic conversion of Stoneley waves within a borehole and showed that the ratio of the converted electric field to the pressure is sensitive to the porosity rather than to the permeability. This ratio is increased by a factor of 2 for increasing porosity from 10 to 30 %.…”
Section: Permeability Deductionmentioning
confidence: 99%
“…This ratio is increased by a factor of 2 for increasing porosity from 10 to 30 %. The Stoneley wave being sensitive to the permeability, Guan et al (2013) further investigated the phase of the ratio of the converted electric field to the pressure, and showed that the tangent of this phase is sensitive to the permeability. They showed that the phase of the electric field always lags behind that of pressure in the frequency range up to 5 kHz and there is a frequency about 1 kHz for which the tangent of thus phase is minimum.…”
Section: Permeability Deductionmentioning
confidence: 99%
See 1 more Smart Citation